Intracellular accumulation of Praziquantel in T lymphoblastoid cell lines, CEM (parental) and CEMvbl(P-gp-overexpressing). Issue 1 (December 2016) - Kigen, Gabriel; Edwards, Geoffrey
Abstract Background Praziquantel (PZQ) is an antihelminthic drug whose P-glycoprotein (P-gp) substrate specificity has not been conclusively characterized. We investigated its specificity by comparing itsin vitro intracellular accumulation in CEM (parental), andCEMvbl cells which over express P-gp, a drug efflux transporter. Saquinavir (SQV), a known substrate of efflux transporters was used as control. Methods A reversed phase liquid chromatography method was developed to simultaneously quantify PZQ and SQV in cell culture media involving involved a liquid - liquid extraction followed by ultra-high performance liquid chromatography using a Hypurity C18 column and ultraviolet detection set at a wavelength of 215 nm. The mobile phase consisted of ammonium formate, acetonitrile and methanol (57:38:5 v/v). Separation was facilitated via isocratic elution at a flow rate of 1.5 ml/min, with clozapine (CLZ) as internal standard. This was validated over the concentration range of 1.6 to 25.6 μM for all analytes. Intracellular accumulation of SQV inCEMvbl was significantly lower compared to that in CEM cells (0.1 ± 0.031 versus 0.52 ± 0.046, p  = 0.03 [p <0.05]). Results Accumulation of PZQ in both cell lines cells were similar (0.05 ± 0.005 versus 0.04 ± 0.009, p  = 0.4) suggesting that it is not a substrate of P-gp in CEM cells. In presence tariquidar, a known inhibitor of P-gp, the intracellular accumulation of SQV inCEMvbl cells increased (0.52 ± 0.068 versus 0.61 ± 0.102, p  = 0.34 in CEM cells and 0.09 ± 0.015 versus 0.56 ± 0.089, p  = 0.029 [p  < 0.05] inCEMvbl cells). PZQ did not significantly affect the accumulation of SQV in either CEM (0.52 ± 0.068 versus 0.54 ± 0.061, p  = 0.77), or inCEMvbl cells (0.09 ± 0.015 versus 0.1 ± 0.031, p =  0.89) cells compared to tariquidar, implying that PZQ is not an inhibitor of P-gp inCEMvbl cells. Conclusions PZQ is neither a substrate nor an inhibitor of the efflux drug transporter P-gp in T-lymphoblastoid cells, CEM andCEMvbl . We also report a simple, accurate and precise method for simultaneous quantification of PZQ and SQV.